The Influence of Children's Storybooks on Reading Interest in Elementary Schools - Aswasulasikin; Mazda Leva Okta Safitri; Nurdin Kamil; Bunda Harini; Meilani Tirta Sari (Journal of Educational Studies, 2026)
This study aimed to examine the effect of children’s storybooks on elementary school students’ reading interest. The research employed a quasi-experimental design with a non-equivalent control group design. The participants consisted of 54 fourth-grade students aged 9–10 years from a public elementary school in Indonesia, consisting of 25 males and 29 females. The students were divided into three groups: 18 students in the control class, 18 in experimental class 1, and 18 in experimental class 2. Data were collected using a reading interest questionnaire administered during pretest and posttest, supported by observation and documentation. The data were analyzed quantitatively using paired samples t-tests to examine within-group differences and additional analyses, including independent samples t-tests and one-way ANOVA, to compare differences between groups. The results showed no significant difference in the reading interest of students in the control class. In contrast, significant improvements were found in both experimental classes after the implementation of children’s storybooks. Furthermore, the between-group analysis indicated that the experimental groups demonstrated greater improvement compared to the control group. These findings suggest that the use of children’s storybooks has a positively and statistically significant effect on improving students’ reading interest. Therefore, children’s storybooks can be considered an effective instructional medium to enhance reading interest among elementary school students.